Cost-Effectiveness Analysis of The Antibiotic Ampicillin and Cefuroxime for Bronchopneumonia Patients Toddlers at Secondary Hospital in Surabaya - Wardhani, Dewanti; Firdaus, Favian Rafif; Yunita, Nita; Abdul, Rahem (Pharmaceutical Journal of Indonesia, 2025)
Bronchopneumonia is an infectious disease in toddlers that produces high mortality, morbidity, and costs. The research aims to investigate the cost-effectiveness of ampicillin and cefuroxime for treating bronchopneumonia in toddlers. Data was collected retrospectively from medical records and hospital information systems between March 2023 and August 2023. The hospital-based trial was completed in October 2023. Stratified random sampling was employed to gather samples from those who met the inclusion criteria, which included using ampicillin or cefuroxime and having bronchopneumonia symptoms. Therapeutic success was determined by achieving a normal breathing rate within < 3 days, taking into account total direct medical expenses. The study discovered that the average direct medical cost for ampicillin patients is Rp. 2,792,875 ± 454.704, and for cefuroxime patients, Rp. 2.931.682 ± 908.964 per inpatient. The effectiveness of antibiotics showed that ampicillin (98%) surpassed cefuroxime (96%). Ampicillin's average cost-effectiveness ratio (ACER) is Rp. 28,499, which is less than cefuroxime's Rp. 30,538. The findings of calculating the incremental cost-effectiveness ratio (ICER) of ampicillin and cefuroxime are Rp. -69,404. Ampicillin has lower direct medical costs and higher effectiveness than cefuroxime, making it a more cost-effective therapy for bronchopneumonia in toddlers. Cost-effectiveness pharmacoeconomic studies are necessary to analyze therapy options